2015
DOI: 10.1128/aem.03159-14
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella chomelii Is the Most Frequent Species Infecting Cattle Grazing in Communal Mountain Pastures in Spain

Abstract: The presence of Bartonella spp. was investigated in domestic ungulates grazing in communal pastures from a mountain area in northern Spain, where 18.3% (17/93) of cattle were found to be positive by PCR combined with a reverse line blot (PCR/RLB), whereas sheep (n ‫؍‬ 133) or horses (n ‫؍‬ 91) were found not to be infected by this pathogen. Bartonella infection was significantly associated with age, since older animals showed a higher prevalence than heifers and calves. In contrast to other studies, B. chomeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 45 publications
1
10
2
Order By: Relevance
“…In the present study, brown dog ticks were found to be infected with B. chomelii —a pathogen first isolated from French domestic cattle ( Maillard et al, 2004 ) and found to be the most frequent Bartonella species infecting cattle grazing in Spain pastures ( Antequera-Gomez et al, 2015 ). We also describe the first detection of B. koehlerae in a R. sanguineus tick obtained from dog.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In the present study, brown dog ticks were found to be infected with B. chomelii —a pathogen first isolated from French domestic cattle ( Maillard et al, 2004 ) and found to be the most frequent Bartonella species infecting cattle grazing in Spain pastures ( Antequera-Gomez et al, 2015 ). We also describe the first detection of B. koehlerae in a R. sanguineus tick obtained from dog.…”
Section: Discussionmentioning
confidence: 76%
“…This species has been described in beef and dairy cattle worldwide, including North and South America, Italy, France, Israel, Taiwan and peninsular Malaysia ( Martini et al, 2008 ; Cherry et al, 2009 ; Saisongkorh et al, 2009 ; Tsai et al, 2011 ; Bai et al, 2013 ; Rudoler et al, 2014 ; Kho et al, 2015 ). Another species, B. chomelii , has been isolated from cattle in France and Spain ( Maillard et al, 2004 ; Antequera-Gomez et al, 2015 ). B. rochalimae infects humans, domestic animals and wild carnivores ( Schaefer et al, 2012 ), so there has been much interest in its zoonotic potential ( Eremeeva et al, 2007 ; Chomel et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…bovis strain [ 17 ] and a B . chomelii strain [ 18 ], both with 89% identity. Our genotype also possesses 87% identity with a Bartonella ancashensis strain [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bartonella bovis has been the most common species identified in cattle worldwide (Bai et al, 2013; Chang et al, 2000; Gutiérrez et al, 2014; Kho et al, 2015), except for Spain and New Caledonia, where B. chomelii was the most frequent (Antequera‐Gómez et al, 2015) or the only species found (Mediannikov, Davoust, Cabre, Rolain, & Raoult, 2011). Accordingly, in the present study, only B. bovis DNA was detected in cattle and associated ticks, and in the only positive buffalo.…”
Section: Discussionmentioning
confidence: 99%
“…Although Bartonella infections have been reported in cattle worldwide (Antequera‐Gómez et al, 2015; Bai et al, 2013; Bermond et al, 2002; Gutiérrez et al, 2014; Roilan, Rousset, Scola, Duquesnel, & Raoult, 2003; Tsai et al, 2011), only two studies reported Bartonella in buffaloes so far (Bai et al, 2013; Gonçalves et al, 2018). While the first study isolated B. bovis in Asian buffaloes ( Bubalus bubalis ) from Thailand, the second amplified Bartonella DNA in wild African buffaloes ( Syncerus caffer ) from Mozambique.…”
Section: Introductionmentioning
confidence: 99%